Morfological and craniometrical presentation of some artificially deformed crania from the Hun-Germanic period - Molnár, Mónika; János, István; Szűcs, László; Szathmáry, László (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
Researchers have dealt with the issue of the artificial cranial deformation for a long time. Cranial deformation by various devices could be found in every historical era, in all continents. It is still a custom even in present days in some places. According to the anthropological studies, multitudinous appearance of the custom of artificial cranial deformation was in connection with the Sarmatian, Alan, Goth, Gepidic and Hun peoples in the Carpathian Basin in Europe. In the Carpathian Basin all artificially deformed skulls were dated from the late Iron Age and mainly from the early Migration Period. In the present work, the authors examined nine artificially deformed skulls from the Hun-Germanic period (5th-6th century AD) excavated from two cemeter- ies belonged to the peoples lived in the northeastern part of the Great Hungarian Plain. The main aims were to attempt to shed light on the age at death and sex of the skulls and the type and the extent of the deformation as well as to determine the technique used for head shaping in every case. Additionally, the possible neurologi- cal disability caused by the intentional cranial deformation followed from the change of the head shape is also debated. The deformation mode of the skulls from the Ároktő Csík-gát site is uniform due to the usage of bandage caused characteristically circular deformation. In contrast with these the finds of Nyíregyháza M3 36/c cemetery showed wider variety considering the type, the technique and the extent of deformation. Most of the cases we found traces indicating the usage of bandage, but it was also typical that some kind of objects were pressed to the frontal and/or occipital regions. All of the nine crania showed the features of the Europid great race which was familiar among the common people of Huns and Germans. There were no sexual differences of the deformed crania with respect to the modes and types and extent of modification. The custom of the artificial cranial deformation was widespread in the Carpathian Basin and all over the world, so that this practice should not have caused any serious clinical problems or other neurological disabilities in the vast majority of cases. We could not find any signs of these possible relationship in context with the examined skulls.
Keywords: artificial cranial deformation; Hun-Germanic period; 5th‒6th century